A Master Plan for a Multistratified Spanish Fortress: Guidelines for a Strategic Conservation. (1st November 2020) - Mileto, Camilla; Vegas, Fernando; Cristini, Valentina
ABSTRACT: This text aims to provide a summary of the formal guidelines for the strategic management of a large-scale monumental military complex. In recent years the Castle of Monzón (Huesca, Spain) has called for a strategic planning process within a flexible timescale taking into consideration the issues currently affecting it. The debate between conservation and restoration, its relationship with the surroundings, the land on which it stands, pre-existing elements, possible uses and management are some of the key points discussed. The aim of the master plan was to establish the main strategic axes for the design and implementation of the action plans needed to attain the objectives set. Far from easy, these objectives have been defined following an extensive process of study and analysis carried out by an interdisciplinary team.